Early Sport Specialization: Effectiveness and Risk of Injury in Professional Baseball Players - Wilhelm, Andrew (Orthop J Sports Med, 2017)
BACKGROUND: The rate of early sport specialization in professional baseball players is unknown. PURPOSE: To report the incidence and age of sport specialization in current professional baseball players and the impact of early specialization on the frequency of serious injuries sustained during the players’ careers. We also queried participants about when serious injuries occurred, the players’ current position on the field, and their opinions regarding the need for young athletes to specialize early to play at the professional level. STUDY DESIGN: Descriptive epidemiological study. METHODS: A total of 102 current professional baseball players anonymously completed a 7-question written survey. Early sport specialization was defined as “single-sport participation prior to high school.” Injury was defined as “a serious injury or surgery that required the player to refrain from sports (baseball) for an entire year.” Chi-square tests were used to investigate the risk of injury in those who specialized early in baseball versus those who did not. Independent-sample t tests were used to compare injury rates based on current player position. RESULTS: Fifty (48%) baseball players specialized early. The mean age at initiation of sport specialization was 8.91 years (SD, 3.7 years). Those who specialized early reported more serious injuries (mean, 0.54; SD, 0.838) during their professional baseball career than those who did not (mean, 0.23; SD, 0.425) (P = .044). Finally, 63.4% of the queried players believed that early sport specialization was not required to play professional baseball. CONCLUSION: Our study demonstrated a statistically significant higher rate of serious injury during a baseball player’s professional career in those players who specialized early. Most current professional baseball players surveyed believed that sport specialization was not required prior to high school to master the skills needed to play at the professional level. Our findings demonstrate an increased incidence of serious injuries in professional baseball players who specialized in baseball prior to high school. Youth baseball athletes should be encouraged not to participate in a single sport given the potential for an increased incidence of serious injuries later in their careers. No data are available to suggest that early specialization is needed to reach the professional level.